Fibrous protein-based hydrogels for cell encapsulation - Silva, Raquel; Fabry, Ben; Boccaccini, Aldo R. (Biomaterials, 2014)
Tissue scaffolds play a vital role in tissue engineering by providing a native tissue-mimicking environment for cells, with the aim to promote cell proliferation, proper cell differentiation, and regeneration. To better mimic the microenvironment of native tissues, novel techniques and materials have emerged in recent years. Among them, hydrogels formed from self-assembled biopolymer networks are particularly interesting. This paper reviews the fabrication and use of fibrous protein-based hydrogels, with an emphasis on silk, keratin elastin and resilin proteins. Hydrogels formed by these proteins show close structural, chemical and mechanical similarities with the extracellular matrix, typically good biological compatibility, and they can trigger specific cellular responses. In addition, these hydrogels can be degraded in the body by proteolytic enzymes. For these reasons, fibrous protein hydrogels are one of the most versatile materials for tissue engineering. © 2014 Elsevier Ltd.
Keywords: Biomaterials; Cell-encapsulation; Fibrous-proteins; Hydrogels